Do stakeholders or social obligations drive corporate social and environmental responsibility reporting? Managerial views from a developing country. Issue 3 (3rd August 2015) - Hossain, Md Moazzem; Alam, Manzurul; Islam, Muhammad Azizul; Hecimovic, Angela
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to explore senior managers' perception and motivations of corporate social and environmental responsibility (CSER) reporting in the context of a developing country, Bangladesh. Design/methodology/approach – In-depth semi-structured interviews were conducted with 25 senior managers of companies listed on the Dhaka Stock Exchange. Publicly available annual reports of these companies were also analysed. Findings – The results indicate that senior managers perceive CSER reporting as a social obligation. The study finds that the managers focus mostly on child labour, human resources/rights, responsible products/services, health education, sports and community engagement activities as part of the social obligations. Interviewees identify a lack of a regulatory framework along with socio-cultural and religious factors as contributing to the low level of disclosures. These findings suggest that CSER reporting is not merely stakeholder-driven, but rather country-specific social and environmental issues play an important role in relation to CSER reporting practices. Research limitations/implications – This paper contributes to engagement-based studies by focussing on CSER reporting practices in developing countries and are useful for academics, practitioners and policymakers in understanding the reasons behind CSER reporting in developing countries. Originality/value – This paper addresses a literature "gap" in the empirical study of CSER reporting in a developing country, such as Bangladesh. This study fills a gap in the existing literature to understand managers' motivations for CSER reporting in a developing country context. Managerial perceptions on CSER issues are largely unexplored in developing countries.